Томський період діяльності академіка Миколи Кащенка - Готра, О.Б. (Історичний архів. Наукові студії, 2015)
У статті автор досліджує томський період науково-педагогічної та громадської діяльності Миколи Кащенка. Висвітлено біографію вченого за особовим архівним фондом. Розкрито пріоритетні напрями його діяльності, визначено місце і роль вченого у галузі науки та культури в кінці ХІХ – першій третині ХХ ст. Показано громадянську позицію вченого. Відзначено популяризацію наукових знань та широкі різносторонні інтереси вченого. В статье автор исследует томский период научно-педагогической и общественной деятельности академика Николая Кащенко. Освещено биографию ученого за личным архивным фондом. Раскрыто приоритетные направления его деятельности, определены место и роль ученого в отрасли науки и культуры в конце ХІХ – первой трети ХХ века. Раскрыто роль ученого в создании кафедры зоологии Томского университета, организации Зоологического музея. Проанализирована деятельность Н. Кащенко в отрасли научного плодоводства Cибири. Установлено, что Н. Кащенко, как один из авторитетнейших профессоров Томского университета, был избран членом многих общественных организаций. Раскрыта его роль в создании Сибирских высших женских курсов. Показана общественная позиция ученого. Отмечено популяризацию научных знаний и широкие разносторонние интересы ученого. The author explores the period of Tomsk scientific, educational and social activities of academician Nikolai Kashenko. The biography of the scientist’s personal archive fund is shown. The priorities of its activities, the place and role of the scientist in the field of science and culture at the end of XIX – the first third of the twentieth century are discovered. The role of the scientist in the creation of the Department of Zoology at Tomsk University and the organization of the Zoological Museum are disclosed. The activities of N. Kashenko industry Horticulture Science of Siberia are analyzed.
It has beeb established that N. Kashenko was elected a member of many community organizations as one of the most respected professors at Tomsk University. His role in the creation of the Siberian women’s higher rates is disclosed. The social position of the scientist is shown. The popularization of scientific knowledge and wide versatile interests of scientist is noted.